Pengaruh Keterampilan Proses Sains Melalui Model Inkuiri Terbimbing terhadap Hasil Belajar Siswa pada Materi Larutan Asam Basa - Netty Ino Ischak; Eka Anggraini Odja; Jafar La Kilo; Akram La Kilo (Universitas Pendidikan Mandalika Mataram, 2020)
Chemistry learning has so far emphasized macroscopic and symbolic aspects as a result of misconceptions and students' low understanding of chemistry. This study aims to determine the influence of science process skill through guided inquiry model on student learning outcomes on acidic-basicsolution topic. The type of research is experimental research with Posttest-Only Control Design. Sampling was done by using Purposive Sampling technique. The sample of research for the experimental class and control class were 31 students, respectively. Data collection using objective test as an instrument that contains test about acidic acid material. Data analysis technique used to test the research hypothesis is t-test. Based on the statistical results obtained the average value of post-test experimental class is 58.55 while for the control class the average post-test value is 39.68. Result of data analysis for learning result show that in significant level 0,05 obtained tcount> t table (6,22> 1,671), then H0 rejected or accepted H1. Thus it can be concluded that there is the influence of process skills of science through guided inquiry model on student learning outcomes on acidic acid solution materials.The positive effects are also discussed in this study.